Industrial Electrical Energy Efficiency Research Based on DEA Optimization Model - Jianna Zhao; Xin Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Traditional DEA does not take into account the environmental variables when analysis the electrical energy efficiency. In order to weigh the objective and subjective factors’ impact on industrial electrical energy efficiency , this paper attempts to analyze the China's  2011 industrial electrical energy efficiency step by step using DEA optimization model. The results showed that, electrical energy efficiency value in considering the case of environmental factors was increased , effect of the external environment on electrical energy efficiency indeed have a significant impact, On these analysis, the paper proposed some feasible recommendations like increasing the scale of industrial energy utilization, eliminating monopolies as soon as possible, allocating the science and technology funding actively and feasibly DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4454